Elemental carbon and PM(2.5 )levels in an urban community heavily impacted by truck traffic. - Lena, T Suvendrini (2002)
Hunts Point, a 690-acre peninsula in the South Bronx, New York City, is a hub in the tristate (New York, New Jersey, and Connecticut) freight transportation system. This study was carried out in response to community concerns about potential health effects of exposure to diesel exhaust particulate (DEP). We measured particulate matter < 2.5 microm in aerodynamic diameter (PM(2.5)) and elemental carbon (EC) on sidewalks and tested whether spatial variations in concentrations were related to local truck traffic density. Ten-hour integrated air samples for EC and PM(2.5) were collected for 9 days over a 3-week period in the summer of 1999 at seven geographically distinct intersections. Simultaneous traffic counts were carried out for each sampling event. Traffic was classified into three classes: passenger cars, small trucks, and large trucks (diesel vehicles). Mean diesel vehicle volumes ranged from 9.3 to 276.5 vehicles/hr across sites. Mean EC concentrations by site ranged from 2.6 microg/m(3) at the control site to 7.3 microg/m(3) along a designated truck route. Linear regression of site-specific mean EC concentration on mean large truck counts predicted an increase of 1.69 microg/m(3) EC per 100 large trucks/hr (SE = 0.37; p = 0.01; R(2) = 0.84). Average PM(2.5) concentrations by site ranged 1.6-fold (19.0-29.9 microg/m(3)) and were more weakly associated with local traffic. Variations over time for PM(2.5 )were more pronounced, ranging almost 4-fold (8.9-34.4 microg/m(3)). These results show that airborne EC concentrations, an important component of DEP, are elevated in Hunts Point and that the impact varies across the community as a function of large truck traffic.